Examining the Effectiveness of a Nutrition Education Intervention for Hispanic Participants - Ginnefer Cox; Britt Rotberg; Melanie Ng; Sarah Henes; Silvia Giraudo (Georgia Southern University, 2020)
BackgroundThe Expanded Food and Nutrition Education Program (EFNEP) Food Talk nutrition education curriculum in the state of Georgia was specifically tailored towards Hispanic EFNEP participants in order to test the effectiveness of the intervention in the Hispanic population.Methods455 Hispanic EFNEP individuals ages 18-61 in the state of Georgia participated in the data collection. Measures collected include a 24 hour diet recall, and a food behavior checklist to compare consumption and food behavior practices both before and after nutrition education intervention.ResultsMeasurable objectives of the study include statistically significant (pConclusionsThis study supports a nutrition intervention developed to improve dietary behaviors for EFNEP participants will be effective in the Hispanic population of Georgia with modifications to the nutrition education curriculum.